SEJARAH DAN PEMIKIRAN TOKOH SOSIOLOGI DARI TRADISI ISLAM HINGGA BARAT SERTA RELEVANSINYA TERHADAP PENDIDIKAN MODERN - Muhammad Hafifulloh Ghoni; Gemma Gita Reformasi; Zainal Arifin; Munir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Educational sociology is a discipline that arose from the need to understand the relationship between education and social dynamics. However, there is still a problem in that the thoughts of major sociological figures, both from Islamic and Western traditions, have not been comprehensively studied to determine their relevance in addressing the challenges of modern education. This situation has resulted in a lack of strong theoretical foundations for designing curricula, learning strategies, and educational policies that are in line with the needs of contemporary society. This study aims to: (1) trace the history of the birth and development of educational sociology, (2) review the biographies and thoughts of major sociological figures from Islamic to Western traditions, and (3) analyze the relevance of these figures' thoughts in the context of modern education. The research uses a qualitative method with a literature study approach based on 4 books and 15 scientific journal articles. The results show that Ibnu Khaldun, Comte, Ward, Durkheim, Dewey, Parsons, and Syari’ati have made significant contributions in viewing education as a means of individual formation and social transformation. The relevance of their thoughts is reflected in the need for modern education that is inclusive, evidence-based, fosters morality, is democratic, critical, and advocates for social justice. Thus, the integration of thoughts across Islamic and Western traditions can enrich the discourse of educational sociology and provide a new direction for curriculum renewal and educational policy in the era of globalization.